1981
DOI: 10.1111/j.1365-2621.1981.tb15360.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Sensory Properties of Chicken Patties Made with Varying Proportions of White and Dark Spent Fowl Muscle

Abstract: Spent fowl was flaked and formulated to include: (1) 100% dark meat; (2) 75% dark rneat, 25% white meat; (3) 50% dark meat, 50% white meat; (4) 25% dark meat, 75% white meat; and (5) 100% white meat. Patties were made and half from each formulation were coated with calcium alginate. Proximate analysis of patties before and after cooking, calculation of cooking loss, and evaluations for textural properties and sensory attributes were performed. As the proportion of white meat increased, the samples contained le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…A carne de peito de matriz apresentou baixa intensidade de maciez (6,9) quando comparada com a carne de frango (2,5). Esses dados corroboram ROLAND et al (1981), que relataram problemas com relação à textura, visto que animais mais velhos apresentam carne notadamente mais dura. A carne de matriz apresentou menor suculência (3,4), quando comparada à carne de peito de frangos (6,5).…”
Section: Resultsunclassified
“…A carne de peito de matriz apresentou baixa intensidade de maciez (6,9) quando comparada com a carne de frango (2,5). Esses dados corroboram ROLAND et al (1981), que relataram problemas com relação à textura, visto que animais mais velhos apresentam carne notadamente mais dura. A carne de matriz apresentou menor suculência (3,4), quando comparada à carne de peito de frangos (6,5).…”
Section: Resultsunclassified
“…(1984) reported that 25% of the meat in chicken patties could be from fowl without a detectable change in quality or acceptability as compared with 10Oo/o broiler breast meat. In chicken patties containing various proportions of white and dark spent fowl muscle, less fat, less cooking loss and higher sensory preference scores were observed as the proportion of white meat increased (Roland et al, 1981). Lyon et al (1983) reported that when precooked fowl meat was added to the raw formulation of meat patties at the 10% level the product was less springy.…”
Section: Chicken Sausages and Pattiesmentioning
confidence: 95%
“…The first published report found on the use of flake cutting with poultry was by Lyon et al (1980 They reported that flake cutting mechanically deboned poultry improved the texture of patties as compared to only mixing mechanically deboned poultry with other ingredients. This technique was applied to spent fowl meat for chicken patties by Roland et al (1981). They used an Urschel Comitrol (Urschel Inc., Valparaiso, IN) on white and dark meat from spent hens and observed that a sensory panel scored white meat much higher than dark meat.…”
Section: Introductionmentioning
confidence: 99%